Valproic acid induced aplastic crisis and Stevens-Johnson syndrome in a single pediatric patient - Wei-Jian Yang; Zhen-Hui Chen; Yi-Nan Zheng (Heliyon, 2023)
Valproic acid (VPA) is a commonly used antiepileptic drug (AED). Aplastic crisis is defined as acute arrest of hematopoiesis. Stevens-Johnson syndrome (SJS) is a fatal cutaneous adverse drug reaction. We herein report a rare case of aplastic crisis and SJS in a single pediatric patient that were probably caused by VPA. A 2-year-old girl was involved in a car accident. She was diagnosed with skull fractures, cerebral contusions, pulmonary contusions, and fractures of the left iliac bone by computed tomography. VPA was administered as prophylaxis for post-traumatic epilepsy. From day 13, she developed repeated high fevers, and multiple antibiotics were ineffective; she was then transferred to our pediatric intensive care unit. After transfer, she developed liver function impairment, decreased peripheral blood cell counts, and skin damage. After withdrawal of the VPA and administration of prednisone, intravenous immunoglobulin, local skin care, and nutritional support, her body temperature normalized and her hematopoietic function and skin lesions successively resolved. She was transferred out of the pediatric intensive care unit on day 56 and discharged on day 70. At the 6-month follow-up, a blood examination was normal, and repeat computed tomography revealed multiple softening foci of the bilateral brain and less subdural effusion than before. To our knowledge, no report to date has described aplastic crisis and SJS in a single patient. The purpose of this paper is to increase clinicians’ knowledge in the treatment of adverse drug reactions (ADRs) and emphasize the importance of standardized application and strict monitoring of VPA in patients with post-traumatic brain trauma.